2020
DOI: 10.1016/j.jcf.2020.06.018
|View full text |Cite
|
Sign up to set email alerts
|

No detection of SARS-CoV-2 in cystic fibrosis patients at the Regional (Lazio) Reference Center for CF in Italy

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…In conclusion, lower ACE2 levels in CF upper respiratory cells might be one of the factors explaining the apparently lower incidence of SARS-CoV-2 infection in CF patients compared with the general population [ 3 , 4 ]. In apparent contrast, a recent study reported a remarkable upregulation of ACE2 (and TMPRSS2) expression in biopsies from CF lungs with respect to controls [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, lower ACE2 levels in CF upper respiratory cells might be one of the factors explaining the apparently lower incidence of SARS-CoV-2 infection in CF patients compared with the general population [ 3 , 4 ]. In apparent contrast, a recent study reported a remarkable upregulation of ACE2 (and TMPRSS2) expression in biopsies from CF lungs with respect to controls [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a clinical diagnosis of CF attending the Regional (Lazio) CF Reference Center of the University Hospital Policlinico Umberto I were enrolled during the 2019/2020 winter season. Real-time (RT) PCR reactions targeting the RNA-dependent RNA polymerase (RdRp) and the envelope (E) genes of SARS-CoV-2 were developed in-house following published protocols [ 4 , 16 ]. Cells were collected from oropharyngeal swabs taken for routine diagnostic testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lower seroprevalence was noted in individuals with CF (2.7%) versus the general population (4.9%), suggesting a lower infection rate [14] . An overview study conducted in Italy concluded that the infection rate was indeed lower in the CF population than that of the general population [15] , [16] .…”
Section: Epidemiology Of Sars-cov-2 In Cystic Fibrosismentioning
confidence: 99%
“…Secondly, ENaC is significantly increased in CF, promoting inflammation and affecting airway surface liquid homeostasis.
Figure 1 Role of ACE and ACE2 in SARS-CoV-2 Lung Infection [15]
…”
Section: Role Of Angiotensin Converting Enzyme 2 (Ace2) and Furin In Sars-cov-2 Infectionmentioning
confidence: 99%